Sexuality in Ancient and Modern Nepal: A Historical and Contemporary Analysis - Adhikari, Anup; Aryal, Vijaya; Aryal, Bhagwan; Dhakal, Aryan (The Himalayan Geographers, 2024)
Sexuality is a dynamic and contested domain by deeply ingrained patriarchal norms, and the sociocultural landscape fosters tensions between traditional beliefs and emerging discourses on gender, sexuality, and individual rights. Through Legislative advancements, including constitutional provisions for gender equality, sexual minorities continue to face systemic discrimination, violence, and stigma. It explores how traditional and evolving socio-cultural dynamics influence gender, sexuality, and individual rights in Nepal. By employing a mixed-methods approach anchored in qualitative content analysis, the research integrates historical and socio-legal frameworks to examine the historical roots and contemporary manifestations of sexuality. The study draws sources such as legal documents (e.g., Muluki Ain, Nepal’s Constitution) and historical texts (e.g., Manusmriti), like peer-reviewed articles and NGO reports. Analytical techniques include thematic analysis to identify recurring patterns, comparative study to trace shifts in societal attitudes, and critical discourse analysis to interrogate power structures shaping gender contribution on addressing inequalities; patriarchal attitudes undermine women’s autonomy and perpetuate gendered double standards. The need for comprehensive grassroots education, social transformation, and legislative reforms to dismantle entrenched hierarchy systems is underscored by the study and support to contribute broader discussions on gender equity and social justice within Nepal’s evolving socio-political landscape.